Prosodisk demarkering og domæneinitial styrkelse i dansk - Vies, Christophe Zerakitsky (Journal of Language Works - Sprogvidenskabeligt Studentertidsskrift, 2021)
In this study we investigate prosodically conditioned strengthening of the Danish [s] by analyzing its spectral composition and duration across different phonological domains in eighteen different positions. We do so by performing acoustic analyses of [s] in a series of utterances with the same prosodic skeleton, varying /s/’ position. Three prosodic domains and three positions were considered: Utterance, prosodic phrase and stress group along with the initial, medial and final positions. Spectral peak, center of gravity, variance, slope and duration of each segment were measured. We found no sign of cumulative effects of the height of the prosodic domain, but we did find an effect of stress: [s] exhibits significantly higher values regarding all the analyzed spectral properties in the initial position compared with the final position. In regard to the duration, we also found a final lengthening on the two higher domains, reversing the pattern of the stress group. In addition to these findings, our results indicate that the conjunction og ‘and’ in Danish phonologically procliticizes to the following prosodic word, causing final lengthening of the preceding segment.